The Profile of Teachers' Emotional Intelligence in EFL Classroom - Bashir, Sitti Nurul Mutmainnah Al; Muhayyang, Maemuna; Sofyan, Ryan Rayhana (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
The objectives of this research are to find out (1) the level of teachers' emotional intelligence in English as a foreign language (EFL) classroom interaction at SMPN 2 Mappakasunggu, and (2) the affecting factors of the level of teachers' emotional intelligence in English as a foreign language (EFL) classroom interaction are at SMPN 2 Mappakasunggu. Utilizing a qualitative descriptive research design, the researchers conducted observation and interview with four English teachers at SMPN 2 Mappakasunggu. The results identified that teachers' emotional intelligence levels are divided into five aspects: self-awareness, self-regulation, motivation, empathy, and social skills. The study also identified internal factors, such as hereditary factors, religious factors, building-relationship factors, self-motivation, and external factors, including family factors, school environment factors, and community environment factors, that influence teachers' emotional intelligence. The findings also suggest that teachers with higher levels of emotional intelligence tend to create a more positive classroom atmosphere, handle conflicts more effectively, and demonstrate a greater ability to motivate and engage students. Conversely, teachers with lower levels of emotional intelligence may struggle with classroom management and face challenges in building strong relationships with their students. Based on these findings, it is recommended that teachers attend training that can improve emotional intelligence, and further research should be suggested to explore the effect of emotional intelligence on student learning outcomes.